Conditions and prospects for increasing forest yield in Northern Europe - Jonsson, Ragnar; Mustonen, Mika; Lundmark, Tomas; Nordin, Annika; Gerasimov, Yuri; Granhus, Aksel; Hendrick, Eugene; Hynynen, Jari; Kvist Johannsen, Vivian; Kaliszewski, Adam; Miksys, Virginijus; Nord-Larsen, Thomas; et al. (Working Papers of the Finnish Forest Research Institute, 2013)
Layout: Anne Siika/Metla
Keywords: energy; forest industry; forest management; forests; national forest inventory; renewable; VMI; energia; metsänhoito; metsät; metsäteollisuus; uusiutuvat luonnonvarat